Street Participatory Action Research in Prison: a Methodology to Challenge Privilege and Power in Correctional Facilities - Payne, Yasser Arafat (The prison journal, 2018)
This article presents a prison research model grounded in street participatory action research (Street PAR) methodology but programmatically facilitated in an Inside-Out Prison Exchange Program class. Street PAR’s nine tenets were adapted to a prison setting, and we demonstrate its promise with a brief case study of research projects at one prison location. This article also explores the challenges scholars and incarcerated persons as researchers may face in correctional facilities. Street PAR and Inside-Out can improve prison environments and successful transition to local communities as a function of equipping incarcerated persons with reading, writing, and analytic skill sets.